فعالية استخدام وسيلة Picture Story في تحسين مهارة الكتابة لدي تلاميذ الصف الحادي عشر في المدرسة العالية الحكومية الأولى بويولالي للعام الدراسي 2025/2026 م - Vira Hilma Fadhila; Renny Dwi Arumsari; Rofida Afidatul Ummah; Mila Alinda Hastuti; Hanik Mukarromatul Intiha’iyah (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2026)
The teaching of Arabic writing skills among eleventh-grade students at Madrasah Aliyah Negeri 1 Boyolali faces a major problem, namely the students' low ability to develop ideas in writing. This study aims to determine the effectiveness of the picture story media in improving writing skills of eleventh-grade students at Madrasah Aliyah Negeri 1 Boyolali using a quantitative method with an experimental design on a sample consisting of 72 students. The results showed that the average score of the experimental class before treatment was 55.8 and increased to 85.9 with an improvement percentage of 54%, while the average score of the control class increased from 57.1 to 76.2 with an improvement percentage of 33%. These results indicate a significant difference in favor of the experimental class, where the Independent Sample t-test showed a significance value of 0.000, and the N-Gain value reached 0.67. This indicates that the use of picture story media is more effective than conventional media in improving writing skills.